Jawabanmu

2014-03-11T14:33:53+07:00
Menurut saya, untuk x = 1 2x ² + qx + (q-1) = 0 => 2(1 ²) + q1 + (1-1) =0 => 2 + q + 0 = 0 => 2 + q = 0 => q = -2 untuk x = 2 2x ² + qx + (q-1) = 0 => 2(2²) + q2 + (2-1) =0 => 8 + 2q + 1 = 0 => 9 + 2q = 0 => 2q = -9 => q = -4,5 coba teliti kembali.
2014-03-11T15:01:24+07:00
2x² + qx + (q-1) = 0
mempunyai akar x₁ dan x₂
x₁ + x₂ =  \frac{-b}{a} = \frac{-q}{2}
x₁ . x₂ =  \frac{c}{a} = \frac{q-1}{2}
x₁² + x₂² = 4
(x₁+x₂)² - 2 x₁x₂ = 4
( \frac{q}{2} )²-q-1=4
 \frac{ q^{2} }{4} -q-1 = 4
q²-4q-4 = 16
q²-4q-20 = 0


3 1 3